Forex and financial markets dynamics: A case of China and ASEAN - Mohammad Uzair Akram; Kashif Zaheer Malik; Ali Imtiaz; Ammar Aftab (Cogent Economics & Finance, 2020)
The paper aims to investigate the possible dual causality between exchange rates and stock indices of China and ASEAN using Structural Vector Auto-Regressive Model (SVAR). The paper has analysed the dynamic relationships between the Yuan and the Shanghai Composite Index and Shenzhen Stock Index in the context of China's third largest trading bloc, i.e., ASEAN, after the Asian Financial Crisis of 1997. The Asian Financial Crisis of 1997-98 had an adverse impact on stock indices and the currencies of ASEAN countries. It was also expected that a devaluation of the Yuan would follow soon, thus plummeting investors' confidence in the Chinese markets. Further research was needed to explore the complex relationship between financial and forex markets in the context of China and ASEAN. The focus of this paper is to explore such relationship with the focus on China. The results of the model confirm the dual causality between the two variables of interest in China. It concludes that a positive financial shock does have a small but significant impact upon the Yuan, whereas a positive exchange rate shock has a high and a significant impact upon the Shanghai and Shenzhen Composite Indices. The paper finds the effect of monetary and demand shocks upon the Yuan and stock market indices to be insignificant.
Keywords: C32; D54; E44; F31; F63; 330; Causality; exchange rates; stock market; VAR; China; ASEAN